Seri ilmu pengetahuan anatomi dan fisiologi / Naomi E Balaban, James E Bobick ; penerjemah, B. Sandra Tanuwidjaja ; penyunting,Tim Indeks ; editor, Bambang Sarwiji - BALABAN, Naomi E; Bobick, James E; Sandra Tanuwidjaja, B; Tim Indeks (Indeks, 2014)
ix, 385 hlm. : ilus. ; 25 cm.